Application of vacuum distillation in refining crude indium - Jiang, Wen-Long; Deng, Yong; Yang, Bin; Liu, Da-Chun; Dai, Yong-Nian; Xu, Bao-Qiang (Rare metals, 2013)
Vacuum distillation is a technique suitable for low boiling and melting point materials, to remove the heavy and low vapor pressure impurities at low level. As indium has low melting point and high boiling point, it is suitable for refining by vacuum distillation. First, saturation vapor pressure for major elements in crude indium was calculated by the Clausius–Clay Prang equation, which could approximately predict the temperature and pressure during vacuum distillation process. Second, the activity coefficients for In–Cd, In–Zn, In–Pb, In–Tl at 1373 K, and In–Sn at 1573 K were acquired by means of molecular interaction on volume model. Vapor–liquid equilibrium composition diagrams of those above systems in crude indium were drawn based on activity coefficients. These diagrams could estimate the compositions of products in each process during the refinement of crude indium. Finally, 1.2–1.6 ton crude indium was used per day when vacuum distillation experiments were carried out, and experimental results are in good agreement with the predicted values of the vapor–liquid equilibrium composition diagrams.